Pan-Africanism: Geopolitics, Political Realism and State Governance - Waldman, Maurício (Journal of Central and Eastern European African Studies, 2025)
Pan-Africanism is a set of ideas whose central focus is the notion of cultural and historical unity of the continent, giving rise to the idea of political unity of the African peoples. A fundamental concept for understanding the political evolution of the continent, this process encompasses a period that extends from the era of decolonization to the current world situation, focus which this text seeks to evaluate critically. It should be noted that the political scenario of the continent has put to the toughest tests the seductive notion of the political unity of the entire continent, which has faced both exogenous obstacles, particularly the interference of powers external to the continent, and endogenous barriers, in the latter case, rooted in the colonial heritage as well as in Africa's pre-colonial times. In particular, this paper highlights the confrontation of the original concept, which the maximalist current led by Kame Nkrumah emphasized in terms of a "kingdom of the political", in contrast to the so-called minimalist current, which emphasized the "politics of kingdoms", which ended up imposing itself with the founding of the OAU. Furthermore, the following assessment confronts the weakness of the African state in terms of what political realism has imposed, including the concept of the nation-state and the inviolability of borders, facing the untimeliness of political truculence: of African states, of neo-colonialist intrusion, of the action of terrorist organizations and Islamic supremacism, issues that, at the same time, call into question the very foundations of the pan-Africanist ideal.